IPTEKS Harga Pokok Produksi dan Harga Jual Bahan Batik di Desa Tanah Merah - Salmiah, Neneng; Nanda, Satria Tri; Adino, Intan (Komunitas Manajemen Kompetitif, 2019)
This community service program aims to increase the knowledge of the calculation of the cost of production and the determination of the selling price of batik materials produced by the PKK Group in Tanah Merah Village. The production of batik material by the PKK Group is one of the empowerment programs implemented by the head of Tanah Merah Village. The methods used in this activity are counseling and simulation methods to the PKK group, question and answer, and evaluation. Output targets are to increase knowledge about calculating the cost of goods manufactured and determining the correct selling price and scientific articles to be published at the national level. The material provided in the extension includes: (1) What is the cost of production, (2) The purpose of calculating the cost of production, (3) The method of calculating the cost of production, and (4) Determination of the selling price. To measure the level of success of the activities carried out, then the pre and post tests were carried out. In this PKM activity, the Village Head and village apparatus, the BUMDes manager and the Tanah Merah Village PKK Group were involved collaboratively from the beginning to the end of the activity. The result of this community service activity is an increase in the PKK group's knowledge about calculating the cost of goods manufactured and setting the right selling price.